IMPLEMENTASI NIAI PANCASILA SILA KETIGA DALAM KEGIATAN PEMBELAJARAN DI KELAS 4 SD - Rokhmad; Ika Ari Pratiwi; Sekar Dwi Ardianti (STKIP Subang, 2024)
This research aims to describe the implementation of the third principle of Pancasila values ​​in learning activities, the supporting factors in implementing the third principle of Pancasila values ​​and the obstacles faced in implementing the third value of Pancasila principles in grade 4 of SD N Dengkek 01. This research uses qualitative methods and a narrative approach. The results of this research show that there is implementation of the third principle values ​​in learning activities, but there are still students who cannot apply the third principle values. The teacher's attitude is to reflect the value of the third principle in learning activities, give examples and remind students who violate the value of the third principle. Supporting factors from teachers, curriculum, and collaborative learning. The obstacles faced are lack of student motivation, lack of understanding of the value of the third principle, and the student environment. The way teachers overcome this is by familiarizing, coaching and guiding students.